The use of luteinizing hormonereleasing hormone analogues is still an indispensable element of therapy in castrate-resistant prostate cancer - Milecki, Tomasz; Antczak, Andrzej; Kwias, Zbigniew; Milecki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2014)
Metastatic prostate cancer, which shows progression despite castration testosterone levels, was previously defined as hormone-refractory. This definition has recently been changed to the one presently used – castrate-resistant prostate cancer. Numerous fundamental studies have provided evidence that the development of hormone-refractory prostate cancer is constantly dependent on the concentration of androgens. The aim of the metastatic castrate-resistant prostate cancer (mCRPC) treatment is currently to obtain the lowest possible androgen concentration. The effectiveness of such management has been proven by the results of clinical studies on the latest hormonal and chemotherapeutic medications. In the last two decades, new effective chemo-therapeutics have become available on the market: abiraterone, enzalutamide, docetaxel, cabazitaxel, zoldronic acid, denosumab and alpharadin They significantly contribute to extending patients’ survival and to improving their quality of life. Therefore, the question arises whether using luteinizing hormone-releasing hormone (LHRH) analogues is still a necessary element of the therapy. A detailed analysis of study regimens involving the above-mentioned medications and of available publications supports the view that LHRH analogues are the basic strategy in the treatment of patients with mCRPC. All clinical trials evaluating new therapies still followed the principle of obtaining castration testosterone levels as a result of using LHRH analogues simultaneously with the new medications.